Sintering bonding sheet

The sintered bonding sheet with controlled voids and area ratios addresses bonding reliability issues in semiconductor manufacturing by maintaining adhesion under temperature fluctuations, ensuring stable semiconductor device performance.

JP2024176376APending Publication Date: 2024-12-19NITTO DENKO CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023094868
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-08
Publication Date
2024-12-19

Smart Images

  • Figure 2024176376000001_ABST
    Figure 2024176376000001_ABST
Patent Text Reader

Abstract

To provide a sintering bonding sheet that can adequately maintain bonding with an adherend even when used in an environment where the temperature rises and falls repeatedly.SOLUTION: The present invention provides a sintering bonding sheet having a sintering bonding layer that includes sinterable particles containing a conductive metal and an organic binder, and in an image of the surface of the sintering bonding layer observed at 100x magnification, the maximum size of the observed voids is 100 μm or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sheet for sinter bonding used, for example, when manufacturing a semiconductor device. [Background technology]

[0002] Conventionally, a sintering bonding sheet used in the manufacture of a semiconductor device has been known. This type of sintering bonding sheet has a sintering bonding layer containing sinterable particles containing a conductive metal and an organic binder. The sintering bonding layer has pressure-sensitive adhesive properties because it contains the organic binder. In manufacturing a semiconductor device, the above-mentioned sintered bonding layer is disposed between one surface of a substrate and a semiconductor element (such as a semiconductor chip), and a sintering process is performed, thereby bonding the substrate and the semiconductor element via the sintered bonding layer. For example, the following steps are carried out to manufacture a semiconductor device.

[0003] (1) A semiconductor wafer is attached and fixed onto the adhesive layer of a dicing tape having a substrate and an adhesive layer laminated thereon, and then the semiconductor wafer is diced into a plurality of individual semiconductor elements. (2) After peeling one semiconductor element from the adhesive layer and lifting it up using a tool such as a collet, the one semiconductor element is pressed onto the sintered bonding layer of the sintered bonding sheet. This pressing force causes a part of the sintered bonding layer to be singulated to a size corresponding to the size of the semiconductor element. At the same time, the singulated sintered bonding layer is adhered to the semiconductor element, and the tool such as a collet is lifted up to pick up one semiconductor element to which the piece of the sintered bonding layer is adhered. (3) One semiconductor element with the individual pieces of the sintered bonding layer bonded thereto is bonded to one surface of a substrate (a mounting area for the semiconductor element). In other words, one semiconductor element is temporarily fixed to the substrate. (4) By carrying out the above steps (2) and (3) multiple times in the same manner, multiple semiconductor elements to which the individual pieces of the sintered bonding layer are bonded are temporarily fixed in the mounting area of ​​the semiconductor element on the substrate, thereby obtaining an intermediate semiconductor device. (5) By carrying out a sintering process in which the intermediate product of the semiconductor device is heated to a temperature at which the sinterable particles in the sintered bonding layer can be sintered together, the sinterable particles are sintered together while at least a portion of the organic binder is removed from the sintered bonding layer, thereby bonding a plurality of semiconductor elements to the semiconductor element mounting area of ​​the substrate. After the above-mentioned processes, the semiconductor elements are fixed in the semiconductor element mounting area of ​​the substrate by the sintering of the sinterable particles contained in the sintered bonding layer with each other. That is, the semiconductor elements are fixed in the semiconductor element mounting area of ​​the substrate via the individual pieces of the sintered bonding layer that have been sintered.

[0004] In the manufacture of a semiconductor device, instead of carrying out the above steps (1) and (2), a sintered bonding layer may be superimposed on the adhesive layer of a dicing tape, a semiconductor wafer may then be attached, the sintered bonding layer and the semiconductor wafer may be diced into individual pieces, and the semiconductor element with the sintered bonding layer attached may be picked up.

[0005] As a sheet for sinter bonding that can be used in the above-mentioned method for manufacturing a semiconductor device, for example, a sheet having a sinter bonding layer that becomes a strong sintered layer after sintering treatment is known (for example, Patent Document 1).

[0006] In detail, in the sintering bonding layer of the sintering bonding sheet described in Patent Document 1, the average area of ​​the pores in the cross section after heating under specific heating conditions is 0.005 μm 2 ~0.5μm 2 The specific heating conditions are as follows: under a pressure of 10 MPa, the temperature is raised from 80° C. to 300° C. at a heating rate of 1.5° C. / sec, and then the temperature is maintained at 300° C. for 2.5 minutes. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2017-066384 A Summary of the Invention [Problem to be solved by the invention]

[0008] However, when the individual pieces of the sintered bonding layer after the sintering process are used in an environment where the temperature rises and falls repeatedly, the bonding with the adherend such as a substrate or a semiconductor element may become insufficient. In detail, when the individual pieces of the sintered bonding layer are subjected to repeated temperature rises and falls, peeling may occur at a part of the interface between the sintered bonding layer and the adherend, or cracks may occur inside the sintered bonding layer. When the peeling or cracks occur, the bonding between the sintered bonding layer and the adherend cannot be maintained sufficiently, which leads to a decrease in the reliability of the product.

[0009] However, it cannot be said that sufficient research has been conducted yet on a sheet for sinter bonding that can adequately maintain bonding with an adherend even when used in an environment where the temperature rises and falls repeatedly.

[0010] Therefore, an object of the present invention is to provide a sheet for sinter bonding that can adequately maintain bonding with an adherend even when used in an environment where the temperature rises and falls repeatedly. [Means for solving the problem]

[0011] In order to solve the above problems, the sintering bonding sheet according to the present invention has the following features: A sheet for sintering comprising a sintering bonding layer including sinterable particles containing a conductive metal and an organic binder, In an image of the surface of the sintered bonding layer observed at a magnification of 100, the maximum size of the voids observed is 100 μm or less. Effect of the Invention

[0012] The sheet for sinter bonding according to the present invention can adequately maintain bonding with the adherend even when used in an environment where the temperature rises and falls repeatedly. [Brief description of the drawings]

[0013] [Figure 1] 1 is a schematic cross-sectional view of a sheet for sinter bonding according to an embodiment of the present invention cut in the thickness direction. [Figure 2A] 11 is a schematic cross-sectional view showing how one semiconductor chip is lifted up from the dicing tape by a collet. [Figure 2B] 4 is a schematic cross-sectional view showing a state in which a part of a sintering bonding layer of a sintering bonding sheet is divided into individual pieces. FIG. [Figure 2C] 4 is a schematic cross-sectional view showing a state in which a part of a sintering bonding layer of a sintering bonding sheet is divided into individual pieces. FIG. [Figure 2D] 11 is a schematic cross-sectional view showing a state in which one semiconductor chip having an individual piece of a sintered bonding layer attached thereto is temporarily fixed to a substrate. [Figure 3A] 11 is a schematic cross-sectional view showing how another semiconductor chip is lifted up from the dicing tape by a collet. [Figure 3B] 13 is a schematic cross-sectional view showing a state in which another semiconductor chip having an individual piece of the sintered bonding layer attached thereto is temporarily fixed to a substrate. [Figure 4A] 5 is a schematic cross-sectional view showing an example of a state in which individual pieces of a sintered bonding layer are heated while being pressed. FIG. [Figure 4B] FIG. 11 is a schematic cross-sectional view showing an example of a state in which an individual piece of a sintered bonding layer is heated without being pressed. [Diagram 5] Photographs showing some examples of images obtained by observing the surface of a sintered bonding layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, one embodiment of the sintering bonding sheet according to the present invention will be described with reference to the drawings.

[0015] The sintering bonding sheet 10 according to this embodiment includes a sintering bonding layer 2 containing sinterable particles containing a conductive metal and an organic binder, as shown in Fig. 1. The sintering bonding layer 2 overlaps one side of the support layer 1.

[0016] [Sintered bonding layer of sintered bonding sheet] The sheet 10 for sinter bonding of this embodiment is, for example, in the form of a long strip. The sheet 10 for sinter bonding of this embodiment may be stored in a state of being rolled up in a cylindrical shape.

[0017] The sintered bonding layer 2 has pressure-sensitive adhesive properties because it contains an organic binder, and therefore can be temporarily bonded to an adherend when subjected to a pressing force. Furthermore, when the sintered bonding layer 2 is subjected to a sintering process, the sinterable particles inside are sintered together. The sintered bonding layer 2 after the sintering process is disposed between, for example, a substrate and a semiconductor chip B to bond them together. In the sintered bonding layer 2 after the sintering process, at least a part of the organic binder has disappeared. It is preferable that almost no organic binder remains in the sintered bonding layer 2, and it is more preferable that no organic binder remains at all.

[0018] In an image of the surface of the sintered bonding layer 2 observed at a magnification of 100, the maximum size of the voids observed is 100 μm or less. Note that the description "the maximum size is 100 μm or less" also includes the case where no voids are observed at all. Because the sintered bonding layer 2 has the above-mentioned configuration, even if the sintered bonding layer 2 is used in an environment where the temperature repeatedly rises and falls, the bond between the sintered bonding layer 2 and the adherend can be sufficiently maintained. The maximum size is preferably 95 μm or less, more preferably 70 μm or less, and even more preferably 50 μm or less. Most preferably, no voids are observed in the observed image. If voids are observed, the maximum size of the voids may be 5 μm or more.

[0019] In this embodiment, preferably, at least 9 mm of the observed image 2 In this range, the area ratio of voids is 5.0% or less. By having the void area ratio of 5.0% or less in the sintered bonding layer 2 as described above, the bond between the sintered bonding layer 2 and the adherend can be more sufficiently maintained even when the sintered bonding layer 2 is used in an environment where the temperature repeatedly rises and falls. The area ratio of the voids is preferably 2.0% or less, more preferably 1.0% or less, even more preferably 0.5% or less, and most preferably 0%. The area ratio of the voids may be 0% or more.

[0020] The maximum size of the voids described above can be reduced, for example, by lowering the solid content concentration of a varnish (described in detail later) containing sinterable particles, an organic binder, and an organic solvent when producing the sintered bonding layer 2. The maximum size can also be reduced by lowering the viscosity of the varnish. Similarly, the area ratio of the voids described above can be reduced by lowering the solids concentration contained in the varnish (described in detail later) or by reducing the viscosity of the varnish.

[0021] [Method of observing the surface of the sintered bonded layer] The surface of the sintered bonding layer 2 is observed as follows. Then, the observed image is subjected to image analysis to determine the maximum size of the voids and the area ratio of the voids.

[0022] The surface of the sintered bonding layer is observed at a magnification of 100 times using an optical microscope. The central part of one side of the sintered bonding layer (the side not overlapping the support layer 1) is selected as the observation area. For example, a digital microscope is used as the optical microscope. More specifically, the sintered bonding layer is placed on a transparent glass and images are taken while being illuminated from above and below. Specific conditions such as illumination and focusing during imaging can be, for example, the conditions described in the image analysis section of the examples described later. [Image analysis method for observed images] Each image captured as described above is subjected to image analysis as follows. More specifically, first, an area with a saturation between 0 and 50 inclusive is extracted so that the gap portion of the image and the non-gap portion are clearly distinguished from each other. Preferably, the lighting conditions, focusing conditions, and the like are adjusted so that the boundary line defined by a saturation of 50 follows the contour (outer periphery) of the gap. For example, by performing binarization processing under such conditions, the non-gap portion becomes a white portion, and the gap portion becomes a colored portion. Next, the maximum size of the voids extracted from each image is calculated. Since voids come in a variety of shapes, the size of each void is determined by drawing a straight line between the two most distant points on each void. In addition, at least 9 mm 2 The area ratio of voids is calculated within the range of at least 9 mm. 2 Calculate the area ratio of the black voids in the observed image. 2 The shape of the observed image is preferably square. The area of ​​the observed image is at least 9 mm. 2 If it is 9mm, 2 More than 11mm 2 The following is preferable. The above area ratio is calculated for at least five randomly selected observation images, and the values ​​are arithmetically averaged to finally determine the area ratio of voids. The above image analysis can be performed, for example, by software attached to an apparatus such as a digital microscope.

[0023] The conductive metal contained in the sintered particles has an electrical conductivity of 100 [μS / cm] or more (10 6 [S / m] or more). Examples of the conductive metal include gold, silver, copper, palladium, tin, and nickel. The conductive metal may be an alloy of two or more metals selected from the group consisting of gold, silver, copper, palladium, tin, and nickel. The sinterable particles may include metal oxides such as silver oxide, copper oxide, palladium oxide, and tin oxide.

[0024] In this embodiment, the sinterable particles preferably contain at least one selected from the group consisting of silver, copper, silver oxide, and copper oxide, which can improve the bonding property when bonding a semiconductor element to a substrate via the individualized sintered bonding layer 2 (individual pieces 2' of the sintered bonding layer), as described below.

[0025] The sinterable particles preferably contain at least one of silver and copper as a conductive metal, which can improve the thermal conductivity and electrical conductivity of the sintered bonding layer 2.

[0026] From the viewpoint of oxidation resistance, the sinterable particles preferably contain silver as a conductive metal. When the sinterable particles contain silver, the sintering process can be suitably carried out even in an air atmosphere. In detail, for example, the sintering process when bonding a semiconductor element such as a semiconductor chip B to a substrate can be suitably carried out in an air atmosphere. On the other hand, when the sinterable particles contain, for example, copper, the sintering process is preferably carried out in an inert environment such as a nitrogen atmosphere to prevent oxidation of copper.

[0027] The sinterable particles may contain a metal oxide, for example, the sinterable particles may be in a state where the surface layer of a metal particle is converted into a metal oxide.

[0028] For example, the sinterable particles may have a core-shell structure having a core portion and a shell portion covering the core portion. The core portion may contain at least one of silver and copper as a main component. The shell portion may contain gold, silver, silver oxide, or copper oxide as a main component. For example, the sinterable particles may be in a state where at least a portion of the surface of a silver particle is covered with silver oxide, or at least a portion of the surface of a copper particle is covered with copper oxide. More specifically, the particle formed of multiple metals may be a particle having a core portion formed of, for example, nickel, copper, silver, aluminum, or the like, and a shell portion covering at least a portion of the surface of the core portion and formed of, for example, gold, silver, copper, or the like.

[0029] In addition, the sinterable particles may be composite particles containing a metal and a material other than a metal. The composite particles may be particles having a core made of resin particles or the like and a surface layer made of a metal such as nickel or gold that covers at least a part of the surface of the core. The core may be made of a carbon material such as carbon black or carbon nanotubes. The composite particles may be made of metal particles that have been surface-treated with a fatty acid.

[0030] When the sinterable particles contain silver, more specifically, when the sinterable particles are silver particles, the silver particles may contain silver element and other elements (metal elements, etc.) that are unavoidable impurity elements. Alternatively, the silver particles may be surface-treated (e.g., silane coupling treatment). Examples of the surface treatment agent for silver particles include fatty acid-based coating agents, amine-based coating agents, and epoxy-based coating agents.

[0031] As the silver particles, silver particles surface-treated with a coating agent (hereinafter, sometimes referred to as coating-treated silver particles) are preferred from the following viewpoints. By using coating-treated silver particles as the sinterable particles, the affinity between the organic binder and the sinterable particles can be further increased in the sintered bonding layer 2 before the sintering process. This allows the sinterable particles to be more sufficiently dispersed in the sintered bonding layer 2 before the sintering process. As will be described later regarding the manufacture of a semiconductor device, at least a portion of the organic binder disappears from the sintered bonding layer 2 by subjecting the sintered bonding layer 2 to a sintering treatment at a predetermined temperature or higher.

[0032] As the sinterable particles, only one type may be used, or two or more types may be used in combination.

[0033] The shape of the sinterable particles is, for example, needle-like, thread-like, spherical, plate-like (including scale-like), etc. Among these shapes, the spherical shape is preferred. When the sinterable particles are spherical, the sinterable particles can be more satisfactorily dispersed in the varnish for obtaining the sintered bonding layer 2, which will be described later.

[0034] The sinterable particles are sintered together by a sintering process in which the particles are heated to a predetermined temperature. The sinterable particles are particles in which at least a portion of each particle is made of the conductive metal and which adhere to each other when heated at a predetermined temperature. Therefore, a heat transfer path is formed inside the sintered bonding layer 2 by the sintering process. In particular, a heat transfer path is formed in the thickness direction. This allows the thermal conductivity (heat dissipation) of the sintered bonding layer 2 to be relatively high.

[0035] The sinterable particles may be sinterable at a heating temperature of 400° C. or less. In other words, sinterable particles that show necking on their outer surfaces when heated at a temperature of 400° C. or less may be used.

[0036] The temperature at which the sinterable particles sinter can be measured using a thermogravimetric differential thermal analyzer. Specifically, measurements are performed under the following conditions using a thermogravimetric differential thermal analyzer (e.g., Rigaku's TG8120 differential thermal balance). A Tg curve and a DTA curve are obtained by such measurements. The temperature of the largest peak of the DTA curve observed near the bottom of the Tg curve is taken as the sintering temperature of the sinterable particles. <Measurement conditions> Heating rate: 10℃ / min Measurement atmosphere: Air Measurement temperature range: from room temperature (23±2℃) to 500℃

[0037] In addition, sinterable particles containing conductive metals such as gold, silver, copper, palladium, tin, nickel, and alloys thereof can be sintered at a heating temperature of 400° C. or less.

[0038] The average particle size of the sinterable particles is preferably 1 nm or more, more preferably 10 nm or more, and even more preferably 50 nm or more. This can improve the dispersibility of the sinterable particles in the varnish for obtaining the sintered bonding layer 2 described below. Therefore, the sintered bonding layer 2 in which the sinterable particles are sufficiently dispersed can be produced from the varnish. On the other hand, the average particle size of the sinterable particles is preferably 10,000 nm or less, more preferably 3,000 nm or less, more preferably 1,000 nm or less, and even more preferably 500 nm or less, so that the sintered bonding layer 2 can have a smoother surface.

[0039] The average particle size of the sinterable particles is determined by observing a cross section of the sintered bonding layer 2 using a scanning electron microscope (SEM). Specifically, the average particle size is determined according to the following procedure. The following procedure is performed on the sintered bonding layer 2 before it is subjected to a sintering treatment (described later). (1) A sintered bonding layer 2 having a size of 10 mm×10 mm when viewed in a direction perpendicular to the thickness direction and a thickness of 50 μm (0.05 mm) is prepared as a measurement sample. (2) The measurement sample is cut, and the cross section is subjected to a surface preparation process and then a conductive treatment is performed to prepare a sample for SEM observation. (3) Obtain SEM images (magnification of 10,000 or 100,000 depending on the size of each particle) at an accelerating voltage of 3 kV. (4) Image analysis is performed on the SEM observation image to identify each particle. Particles that exist on the edge of the observation image are excluded. The circle equivalent diameter of each identified particle is calculated. The circle equivalent diameter is the diameter of a perfect circle calculated from the area of ​​each particle, assuming that each particle is a perfect circle.

[0040] The sintered bonding layer 2 preferably contains sinterable particles in an amount of 60% by mass or more and 99% by mass or less, more preferably 65% ​​by mass or more and 98% by mass or less, even more preferably 70% by mass or more and 97% by mass or less, and most preferably 80% by mass or more and 97% by mass or less. Since the content of sinterable particles is within the above range, when the sinterable particles are sintered together by a sintering process to bond a semiconductor element such as a semiconductor chip B to a substrate, the bonding by the sintered bonding layer 2 after the sintering process can exhibit sufficient reliability.

[0041] The content of sinterable particles in the sintered bonding layer 2 can be calculated from the measured amount of ash remaining after burning the sintered bonding layer 2. For example, the measurement can be performed using a thermogravimetric analyzer (e.g., TG209F1) according to the following procedure. Note that the measurement using the thermogravimetric analyzer is preferably performed under a nitrogen gas flow. (1) A measurement sample of the sintered bonding layer 2 weighed to about 50 mg is heated from room temperature (23±2° C.) to 650° C. (2) The organic binder in the measurement sample is thermally decomposed by holding it at a temperature of 650°C for 30 minutes. (3) Calculate the mass ratio of the remaining components (ash) relative to the weighed value of the measurement sample (approximately 50 mg).

[0042] In this embodiment, the sintered bonding layer 2 preferably contains, as organic binders, a first organic binder and a second organic binder having a smaller molecular weight than the first organic binder.

[0043] The first organic binder is preferably a thermally decomposable polymer binder. The thermally decomposable polymer binder is a binder that is thermally decomposed by the sintering process. The thermally decomposable polymer binder also has a function of maintaining the sintered bonding layer 2 in a sheet shape before the sintering process. From the viewpoint of more fully exerting such a function, the thermally decomposable polymer binder is preferably solid at room temperature (23±2°C). Examples of the thermally decomposable polymer binder include polycarbonate resin and acrylic resin. The sintered bonding layer 2 preferably contains at least one of polycarbonate resin and acrylic resin as the first organic binder. The sintered bonding layer 2 may contain only polycarbonate resin as the first organic binder.

[0044] Examples of polycarbonate resins include aliphatic polycarbonates that have only aliphatic chains and do not contain aromatic structures such as benzene rings between the carbonate esters (-OCOO-) in the main chain, and aromatic polycarbonates that contain aromatic structures between the carbonate esters (-OCOO-) in the main chain. Examples of the aliphatic polycarbonate include polyethylene carbonate and polypropylene carbonate. An example of the aromatic polycarbonate is a polycarbonate containing a bisphenol A structure in the main chain.

[0045] The acrylic resin may be, for example, a polymer of a (meth)acrylic acid alkyl ester having a linear or branched alkyl moiety with a carbon number of 4 to 18. The term "(meth)acrylic" includes both "acrylic" and "methacrylic".

[0046] Examples of the alkyl group (alkyl moiety) of the (meth)acrylic acid ester include a methyl group, an ethyl group, a propyl group, an isopropyl group, an n-butyl group, a t-butyl group, an isobutyl group, an amyl group, an isoamyl group, a hexyl group, a heptyl group, a cyclohexyl group, a 2-ethylhexyl group, an octyl group, an isooctyl group, a nonyl group, an isononyl group, a decyl group, an isodecyl group, an undecyl group, a lauryl group, a tridecyl group, a tetradecyl group, a stearyl group, and an octadecyl group.

[0047] The acrylic resin may have a polymerization unit derived from a monomer other than the (meth)acrylic acid ester in the molecule. Examples of the other monomer include a carboxyl group-containing monomer, an acid anhydride monomer, a hydroxyl group-containing monomer, a sulfonic acid group-containing monomer, and a phosphoric acid group-containing monomer.

[0048] Examples of the carboxy group-containing monomer include acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid. Examples of the acid anhydride monomer include maleic anhydride and itaconic anhydride. Examples of hydroxy group-containing monomers include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and 4-(hydroxymethyl)cyclohexylmethyl (meth)acrylate. Examples of sulfonic acid group-containing monomers include styrenesulfonic acid, allylsulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acrylamidepropanesulfonic acid, sulfopropyl(meth)acrylate, and (meth)acryloyloxynaphthalenesulfonic acid. An example of the phosphate group-containing monomer is 2-hydroxyethyl acryloyl phosphate.

[0049] The second organic binder that may be included in the sintered bonding layer 2 is preferably a volatile binder. The volatile binder is a binder component that, when measured by thermogravimetric analysis (TGA), undergoes complete weight loss (all desorbs to 0% by weight) at a temperature lower than that of the thermally decomposable polymer binder.

[0050] In this embodiment, the volatile binder has a viscosity of 1×10 5 It is preferable that the viscosity of the liquid is less than Pa·s. The viscosity is measured using a dynamic viscoelasticity measuring device (device name: "HAAKE MARS III", manufactured by Thermo Fisher Scientific). Specifically, parallel plates with a diameter of 20 mm are used as a jig, the gap between the plates is set to 100 μm, and the shear rate in the rotational shear is set to 1 s -1 The viscosity is measured as follows.

[0051] Examples of the easily volatile binder include terpene alcohols, alcohols other than terpene alcohols, alkylene glycol alkyl ethers, and ethers other than alkylene glycol alkyl ethers.

[0052] Examples of terpene alcohols include isobornylcyclohexanol, citronellol, geraniol, nerol, carveol, and α-terpineol. Examples of alcohols other than terpene alcohols include pentanol, hexanol, heptanol, octanol, 1-decanol, ethylene glycol, diethylene glycol, propylene glycol, butylene glycol, and 2,4-diethyl-1,5-pentanediol. Examples of alkylene glycol alkyl ethers include ethylene glycol butyl ether, diethylene glycol methyl ether, diethylene glycol ethyl ether, diethylene glycol butyl ether, diethylene glycol isobutyl ether, diethylene glycol hexyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, diethylene glycol butyl methyl ether, diethylene glycol isopropyl methyl ether, triethylene glycol methyl ether, triethylene glycol dimethyl ether, triethylene glycol butyl methyl ether, propylene glycol propyl ether, dipropylene glycol methyl ether, dipropylene glycol ethyl methyl ether, dipropylene glycol propyl ether, dipropylene glycol butyl ether, and tripropylene glycol dimethyl ether. Examples of the ethers other than alkylene glycol alkyl ethers include ethylene glycol ethyl ether acetate, ethylene glycol butyl ethyl acetate, diethylene glycol ethyl ether acetate, diethylene glycol butyl ethyl acetate, and dipropylene glycol methyl ether acetate.

[0053] The easily volatile binder may be used alone or in combination of two or more kinds.

[0054] As the easily volatile binder, terpene alcohols are preferable from the viewpoint of stability at room temperature, and among terpene alcohols, isobornylcyclohexanol is more preferable.

[0055] Isobornylcyclohexanol is also known as 4-[1,7,7-trimethylbicyclo[2.2.1]heptan-2-yl]cyclohexanol. The boiling point of isobornylcyclohexanol is in the range of 308°C to 318°C. The vapor pressure of isobornylcyclohexanol is 0.00003 mmHg at 25°C. Isobornylcyclohexanol has the following characteristic physical properties. In detail, when isobornylcyclohexanol is heated from room temperature (23±2°C) to 600°C under a nitrogen gas flow of 200mL / min at a temperature increase rate of 10°C / min, it loses a large amount of mass above 100°C and evaporates at 245°C (no further mass loss is observed). In addition, it has the property of showing an extremely high viscosity of 1,000,000 mPa·s at 25°C, but a relatively low viscosity of 1,000 mPa·s or less at 60°C. The mass loss is the value when the mass loss rate at the measurement start temperature (room temperature) is set to 0%. In this way, since isobornylcyclohexanol exhibits extremely high viscosity at 25°C as described above, the sintered bonding layer 2 easily maintains a sheet shape at room temperature. On the other hand, isobornylcyclohexanol exhibits relatively low viscosity at 60°C as described above, and becomes tacky. That is, the sintered bonding layer 2 containing isobornylcyclohexanol can adequately maintain a sheet shape at room temperature, and can have tackiness at temperatures of 60°C or higher. The temperature when the semiconductor element is temporarily fixed to an adherend such as a substrate via the sintered bonding layer 2 is usually 60 to 80° C. At such a temperature, isobornylcyclohexanol becomes tacky for the above-mentioned reasons. Therefore, by including isobornylcyclohexanol as the second organic binder, the sintered bonding layer 2 has better temporary fixation to an adherend such as a substrate. In other words, after the semiconductor element is temporarily fixed to the adherend, the attachment position of the semiconductor element can be prevented from shifting and the sintered bonding layer 2 can be prevented from floating up from the adherend.

[0056] The sintered bonding layer 2 may contain 1 mass % or more of the organic binder, may contain 2 mass % or more, or may contain 3 mass % or more of the organic binder. The sintered bonding layer 2 preferably contains 3 mass % or more, more preferably 5 mass % or more of the organic binder. The sintered bonding layer 2 may contain 40 mass % or less of the organic binder, may contain 35 mass % or less, or may contain 30 mass % or less of the organic binder. The sintered bonding layer 2 preferably contains 20 mass % or less of the organic binder, more preferably 10 mass % or less.

[0057] When the sintered bonding layer 2 contains the first organic binder and the second organic binder as organic binders, the ratio (%) of the first organic binder to the total amount of the first organic binder and the second organic binder is preferably 5 mass% or more and 60 mass% or less, more preferably 10 mass% or more and 50 mass% or less, and even more preferably 20 mass% or more and 40 mass% or less. On the other hand, in the sintered bonding layer 2, the content of the second organic binder may be greater than the content of the first organic binder.

[0058] The sintered bonding layer 2 preferably contains 0.01 mass % or more of the first organic binder, more preferably 0.05 mass % or more, even more preferably 0.10 mass % or more, and even more preferably 0.20 mass % or more. The sintered bonding layer 2 preferably contains 20.0 mass % or less of the first organic binder, more preferably 10.0 mass % or less, even more preferably 7.5 mass % or less, and even more preferably 5.0 mass % or less.

[0059] The sintered bonding layer 2 preferably contains 0.5 mass % or more of the second organic binder, more preferably 1.0 mass % or more, even more preferably 1.5 mass % or more, and even more preferably 2.0 mass % or more. The sintered bonding layer 2 preferably contains 20.0 mass % or less of the second organic binder, more preferably 15.0 mass % or less, and even more preferably 10.0 mass % or less.

[0060] The sintered bonding layer 2 may have a single layer structure as shown in Fig. 1. Alternatively, the sintered bonding layer 2 may have a multi-layer structure in which a plurality of layers are stacked. When the sintered bonding layer 2 has a multi-layer structure, it is sufficient that the maximum size of the void size in at least one layer constituting the sintered bonding layer 2 is 100 µm or less as described above.

[0061] The complex viscosity of the sintered bonding layer 2 at 25° C. is, for example, 3.0×10 5 [Pa s] or more 3.0×10 11 The complex viscosity of the sintered bonding layer 2 at 25°C is 3.0×10 6 [Pa s] or more 3.0×10 10 [Pa s] or less is preferable, and 3.0×10 7 [Pa s] or more 3.0×10 9 [Pa s] or less is more preferable, and 7.0×10 7 [Pa s] or more 7.0×10 8 It is more preferable that the viscosity is less than [Pa·s]. The complex viscosity of the sintered bonding layer 2 at 93° C. is, for example, 3.0×10 4 [Pa s] or more 3.0×10 10 The complex viscosity of the sintered bonding layer 2 at 93°C is 3.0×10 5 [Pa s] or more 3.0×109 [Pa s] or less is preferable, and 3.0×10 6 [Pa s] or more 3.0×10 8 [Pa s] or less is more preferable, and 7.0×10 6 [Pa s] or more 7.0×10 7 It is more preferable that the viscosity is less than [Pa·s]. By having the complex viscosity of the sintered bonding layer 2 within the above range, voids that may exist in the sintered bonding layer 2 before the sintering process (described later) are likely to become smaller during the sintering process. Therefore, even if the sintered bonding layer 2 after the sintering process is repeatedly subjected to temperature increases and decreases during use, peeling at a part of the interface between the sintered bonding layer 2 and the adherend can be more effectively prevented, and cracks can be more effectively prevented from occurring inside the sintered bonding layer 2. Therefore, even if the sintered bonding layer 2 is repeatedly subjected to temperature increases and decreases during use, the bond between the sintered bonding layer 2 and the adherend can be more adequately maintained.

[0062] The complex viscosity of the sintered bonding layer 2 is measured under the following measurement conditions. Test piece cut from sintered bonded layer: Length 30mm, width 5mm Measurement equipment: Dynamic viscoelasticity measuring equipment (Product name: "RSA-G2" (manufactured by TA Instruments, etc.) Measurement mode: Tensile mode Initial chuck distance: 20mm Pulling speed: 1mm / sec Measurement temperature: 10℃ to 100℃ (heating rate: 5℃ / min) Read the complex viscosity (complex viscosity coefficient η*) value [Pa s] at least at 25℃ In order to prevent the test specimen from cracking when it was fixed to the chuck, two silicone release-treated PET liners (50 μm thick) were used as cushioning materials in the chuck. The test specimen was sandwiched between these PET liners.

[0063] The complex viscosity can be reduced, for example, by increasing the amount of the organic binder contained in the sintered bonding layer 2. On the other hand, the complex viscosity can be increased by decreasing the amount of the organic binder contained in the sintered bonding layer 2.

[0064] In this embodiment, the thickness of the sintered bonding layer 2 is preferably 5 μm or more, and more preferably 10 μm or more. The thickness of the sintered bonding layer 2 may be 300 μm or less, 200 μm or less, or 100 μm or less. In general, the thinner the thickness of the sintered bonding layer 2, the more likely the cracks described above are to occur inside the sintered bonding layer 2 when the temperature rises and falls repeatedly during use. In contrast, in this embodiment, as described above, the maximum size of the voids in the sintered bonding layer 2 is 100 μm or less. Therefore, even if the sintered bonding layer 2, which is relatively thin, is subjected to repeated rises and falls in temperature during use, it is possible to suppress the occurrence of cracks inside the sintered bonding layer 2. In addition, it is possible to suppress the occurrence of peeling due to the voids and the like at a part of the interface between the sintered bonding layer 2 and the adherend. Therefore, the bond between the sintered bonding layer 2 and the adherend can be sufficiently maintained.

[0065] The thickness of the sintered bonding layer 2 is calculated by measuring the thickness at five randomly selected locations using, for example, a dial gauge (manufactured by PEACOCK, model R-205) and taking the arithmetic average of these measured values.

[0066] [Support layer of sinter bonding sheet] In this embodiment, the support layer 1 of the sheet for sintering bonding 10 functions as a support in the sheet for sintering bonding 10. The support layer 1 is made of, for example, a plastic film.

[0067] Examples of materials for the plastic film include polyolefin resins, polyester resins, polyurethane resins, polycarbonate resins, polyether ether ketone resins, polyimide resins, polyetherimide resins, polyamide resins, wholly aromatic polyamide resins, polyvinyl chloride resins, polyvinylidene chloride resins, polyphenyl sulfide resins, aramid resins, fluororesins, cellulose-based resins, and silicone resins. The support layer 1 may be formed from one type of material, or from two or more types of materials.

[0068] Examples of polyolefin resins include low-density polyethylene resins, linear low-density polyethylene resins, medium-density polyethylene resins, high-density polyethylene resins, very low-density polyethylene resins, random copolymer polypropylene resins, block copolymer polypropylene resins, homopolypropylene resins, polybutene resins, polymethylpentene resins, ethylene-vinyl acetate copolymer resins, ionomer resins, ethylene-butene copolymer resins, and ethylene-hexene copolymer resins. Examples of the polyester resin include polyethylene terephthalate resin, polyethylene naphthalate resin, and polybutylene terephthalate resin.

[0069] The support layer 1 may have a single layer structure or a multilayer structure. The single layer structure is a structure formed of one type of material. For example, a support layer 1 in which two or more layers formed of one type of material are laminated has a single layer structure. On the other hand, a support layer 1 in which two or more layers formed of different materials are laminated has a multilayer structure.

[0070] When the support layer 1 is a plastic film, the support layer 1 may be a non-stretched film or a stretched film. The stretched film may be a uniaxially stretched film or a biaxially stretched film. Furthermore, the support layer 1 may be a release liner having a surface in contact with the sintered bonding layer 2 that has been subjected to a release treatment. For example, a release agent may be applied to one surface of the support layer 1 that is in contact with the sintered bonding layer 2. In this case, when manufacturing a semiconductor device, the individualized sintered bonding layer 2 (individual pieces 2' of the sintered bonding layer) can be easily peeled off from one surface of the support layer 1 (release liner).

[0071] The thickness of the support layer 1 is preferably 10 μm or more and 5000 μm or less, more preferably 20 μm or more and 4000 μm or less, and even more preferably 30 μm or more and 3000 μm or less. The thickness of the support layer 1 is measured in the same manner as the thickness of the sintered bonding layer 2 described above.

[0072] Next, a method for producing the above-mentioned sheet for sinter bonding will be described.

[0073] The method for producing the sinter-bonding sheet includes the steps of: A step of preparing a varnish containing sinterable particles containing a conductive metal, an organic binder, and an organic solvent; and a step of volatilizing the organic solvent from the varnish to produce a sintered bonding layer.

[0074] In the process of preparing the varnish, for example, the varnish is prepared by mixing the above-mentioned sinterable particles, the above-mentioned organic binder, and an organic solvent to disperse the sinterable particles in the organic solvent and dissolve the organic binder in the organic solvent.

[0075] As the organic solvent, for example, alcohols such as ethanol, or ketones such as methyl ethyl ketone (MEK), etc. can be used.

[0076] The mixing temperature when preparing the above varnish is not particularly limited, and is, for example, from 5° C. to 70° C. The mixing method is not particularly limited, and a mixing method using a general stirring device can be adopted.

[0077] The solid content in the varnish is preferably 60% by mass or less, more preferably 58% by mass or less, and even more preferably 55% by mass or less. The solid content is the component excluding the organic solvent, for example, the total content of the above-mentioned sinterable particles and the above-mentioned organic binder. The lower solids concentration in the varnish tends to reduce the size of voids that may be formed when the organic solvent is volatilized from the varnish (described later) during the production of the sintered bonding layer 2. This also reduces the size of voids after the sintering process. Therefore, even if the sintered bonding layer 2 is subjected to repeated temperature increases and decreases during use, peeling due to the voids is more suppressed at a portion of the interface between the sintered bonding layer 2 and the adherend. In addition, the occurrence of cracks due to the voids inside the sintered bonding layer 2 is more suppressed. Therefore, the bond between the sintered bonding layer 2 and the adherend can be more sufficiently maintained. The solids concentration in the varnish may be 30% by mass or more, 40% by mass or more, 50% by mass or more, or 52% by mass or more.

[0078] The viscosity of the varnish at 23°C is preferably 1.0 [Pa·s] or more and 7.0 [Pa·s] or less, and more preferably 2.0 [Pa·s] or more and 5.0 [Pa·s] or less. Such a viscosity is measured using an E-type viscometer (for example, the RE-85 model, manufactured by Toki Sangyo Co., Ltd.). Specifically, the viscosity is measured using a 1°34'×R24 cone rotor as a jig, with a measurement sample volume of 1.1 mL and a rotation speed of 1.0 rpm. The lower viscosity of the varnish tends to reduce the size of voids that may be formed when the organic solvent is evaporated from the varnish (described later) during the production of the sintered bonding layer 2. This also reduces the size of voids after the sintering process. Therefore, even if the sintered bonding layer 2 is subjected to repeated temperature increases and decreases during use, peeling due to the voids is more suppressed at a portion of the interface between the sintered bonding layer 2 and the adherend. In addition, the occurrence of cracks due to the voids inside the sintered bonding layer 2 is more suppressed. Therefore, the bond between the sintered bonding layer 2 and the adherend can be more sufficiently maintained.

[0079] In the process of producing the sintered bonding layer, for example, a coating film is formed by applying a varnish to a predetermined thickness onto the support layer 1. Then, the coating film is heated to volatilize the organic solvent.

[0080] The sintering bonding sheet 10 manufactured as described above can be used, for example, as an auxiliary member when manufacturing a semiconductor device.

[0081] [Method of using sintering bonding sheet (semiconductor device manufacturing method)] Next, an example of a method for manufacturing a semiconductor device using the sheet for sinter bonding 10 according to this embodiment will be described with reference to the drawings.

[0082] The manufacturing method of the semiconductor device according to this embodiment is carried out, for example, using a substrate having a plurality of semiconductor chips B, a plurality of mounting areas on which the plurality of semiconductor chips B are mounted, the above-mentioned sintering joining sheet 10, and a pressing member used to temporarily fix each of the plurality of semiconductor chips B to the plurality of mounting areas.

[0083] In the following, an example will be described in which a semiconductor chip B is mounted on a substrate such as a DBC (Direct Bonded Copper) substrate or an AMB (Active Metal Brazing) substrate using a collet A as a pressing member. These substrates have, for example, a copper die pad E and a copper thin layer F on both sides of a ceramic insulating layer D. The copper die pad E is the mounting area for the semiconductor chip B.

[0084] First, a semiconductor wafer is cut on a dicing tape C to obtain a plurality of semiconductor chips B from the semiconductor wafer (see FIG. 2A). In other words, the semiconductor wafer is divided into a plurality of individual chips to obtain the semiconductor chips B. A commercially available product can be used as the dicing tape C.

[0085] The resulting semiconductor chip B has, for example, a rectangular thin plate shape. The thickness of the semiconductor chip B is, for example, 10 μm or more and 500 μm or less. The thickness of the semiconductor chip B is preferably 20 μm or more and 400 μm or less. The area of ​​the semiconductor chip B when viewed from one side in the thickness direction is, for example, 0.01 mm 2 More than 1000mm 2 Such an area is 0.04 mm 2 More than 500mm 2 It is preferable that:

[0086] Next, as shown in FIG. 2B, the sheet for sintering bonding 10 is placed on the first stage G so that the sintering bonding layer 2 is above the support layer 1. Then, one semiconductor chip B is pressed against the sintered bonding layer 2 with the collet A, thereby attaching the semiconductor chip B to a part of the sintered bonding layer 2. The pressure during pressing is preferably 0.01 MPa or more and 10 MPa or less, and more preferably 0.1 MPa or more and 5 MPa or less. Moreover, the temperature of the collet A or the first stage G during pressing is preferably 40°C or more and 150°C or less, and more preferably 50°C or more and 130°C or less. The shape and size of the surface of the collet A that comes into contact with the semiconductor chip B are substantially the same as the shape and size of one of the semiconductor chips B.

[0087] Next, the collet A is lifted as shown in Fig. 2C. At this time, a part of the sintered bonding layer 2 attached to the semiconductor chip B is lifted together with the semiconductor chip B. In other words, the semiconductor chip B is lifted by the collet A with the individual pieces 2' of the sintered bonding layer still attached. This results in a semiconductor chip B with the individualized sintered bonding layer 2 (hereinafter also referred to as the individual pieces 2' of the sintered bonding layer) attached. Furthermore, by applying a pressure within the above-mentioned range when pressing the semiconductor chip B against the sintered bonding layer 2, or by controlling the temperature of the collet A or the first stage G within the above-mentioned range, a semiconductor chip B having an individual piece 2' of the sintered bonding layer attached thereto can be preferably obtained.

[0088] Next, the substrate (ceramic insulating layer D, copper die pad E, and thin copper layer F) is placed on a second stage H (see FIG. 2D). 2D, while holding collet A at any temperature within a range of 25° C. to 150° C., collet A is lowered vertically to bring individual pieces 2′ of the sintered bonding layer attached to semiconductor chip B into contact with copper die pad E. Next, collet A presses (presses) semiconductor chip B downward toward copper die pad E. As a result, the semiconductor chip B is temporarily fixed to the copper die pad E via the individual piece 2' of the sintered bonding layer (see FIG. 2D). The pressure when the semiconductor chip B is pressed against the copper die pad E is preferably 0.01 MPa or more and 50 MPa or less, and more preferably 0.1 MPa or more and 30 MPa or less.

[0089] The substrate as the adherend of the sintered bonding layer piece 2' may be a lead frame. A general lead frame can be used as the lead frame. For example, a lead frame in which a Cu frame is plated with Ag, or a lead frame in which a Cu frame is plated with Ni, Pd, and Au in this order (Palladium Pre Plated Lead Frame, Pd-PPF) can be used.

[0090] After carrying out each of the above operations to temporarily fix one semiconductor chip B to the copper die pad E, the same operations are repeated. Specifically, as shown in FIG. 3A, a collet A separates another semiconductor chip B from the multiple semiconductor chips B from the dicing tape C and lifts it up. Next, similarly to FIG. 2B, another semiconductor chip B is pressed against the sintering bonding layer 2 of the sintering bonding sheet 10 with a collet A. Furthermore, similarly to FIG. 2C, collet A is pulled up, and semiconductor chip B with sintered bonding layer piece 2' attached thereto is separated from support layer 1 and lifted up. Next, while the collet A is maintained at the same temperature as above, the semiconductor chip B with the individual pieces 2' of the sintered bonding layer attached thereto is brought into contact with another mounting area of ​​the copper die pad E. Then, as shown in FIG. 3B, the collet A presses (presses) the semiconductor chip B downward against the copper die pad E. As a result, the semiconductor chip B is temporarily fixed to another mounting region of the copper die pad E via the individual piece 2' of the sintered bonding layer (see FIG. 3B). The above operations are repeated in order until all the semiconductor chips B to be temporarily fixed to the copper die pad E are placed on the copper die pad E.

[0091] When the semiconductor chips B are temporarily fixed, the collet A may be heated to a temperature at which the sinterable particles contained in the pieces 2' of the sintered bonding layer can be sintered. This may allow a primary sintering process to be performed on the sinterable particles contained in the pieces 2' of the sintered bonding layer. In other words, immediately after the temporary fixing as described above, a part of the sintering process may be performed on the pieces 2' of the sintered bonding layer.

[0092] When the sinterable particles contained in the sintered bonding layer pieces 2' can be sintered at a heating temperature of 400°C or less, it is preferable to heat the collet A to a temperature of 200°C or more. By heating the collet A to 200°C or more, the sinterable particles can be sintered together more thoroughly. Therefore, the semiconductor chip B can be more firmly bonded to the copper die pad E via the sintered bonding layer pieces 2'. In other words, the bonding reliability of the semiconductor chip B to the substrate is further improved.

[0093] When carrying out the above-mentioned primary sintering process, it is preferable to rapidly (in about 5 seconds) heat the collet A. It is preferable to heat the collet A at 30° C. / sec or more, and more preferably at 45° C. / sec or more.

[0094] The primary sintering process may be performed not only by heating the collet A, but also by heating the second stage H at the same temperature as above. This allows the pieces 2' of the sintered bonding layer to be heated from both sides in the thickness direction, so that the sinterable particles can be sintered together more thoroughly. Therefore, the semiconductor chip B can be bonded more thoroughly to the copper die pad E via the pieces 2' of the sintered bonding layer. In other words, the bonding reliability of the semiconductor chip B to the substrate is further improved.

[0095] The temperature of the heated second stage H is preferably equal to or lower than a temperature that inhibits oxidation of the copper die pad E or the thin copper layer F. The heating temperature of the second stage H is preferably 150° C. or lower.

[0096] When carrying out the primary sintering process as described above, for example, after the primary sintering process, collet A may be lifted to separate the semiconductor chip B from collet A, thereby lowering the temperature of collet A to a temperature (e.g., 50°C) at which the sinterable particles become difficult to sinter. When the primary sintering process is performed on each of all the individual pieces 2' of the sintered bonding layer, bonding wires may be bonded to required locations after all the semiconductor chips B are bonded.

[0097] In the manufacturing method of the semiconductor device according to the present embodiment, after the multiple semiconductor chips B are temporarily fixed to the substrate, a heating step may be performed in which the individual pieces 2' of the sintered bonding layer are heated to a temperature at which the sinterable particles can be sintered. In the heating step, heating may be performed while applying a compressive force in the thickness direction to at least one of the multiple individual pieces 2' of the sintered bonding layer. When the above-mentioned primary sintering process is performed, the above-mentioned heating step corresponds to the secondary sintering process. In other words, the sintering process can be performed by both the above-mentioned primary sintering process and the secondary sintering process (the above-mentioned heating step).

[0098] More specifically, in the method for manufacturing a semiconductor device according to this embodiment, the sintering process can be carried out as follows. In the heating step of the sintering process, for example, at least one of the pieces 2' of the sintered bonding layer is heated while being pressed in the thickness direction. Specifically, after the semiconductor chip B is temporarily fixed, as shown in FIG. 4A, the pieces 2' of the sintered bonding layer may be heated while being subjected to a compressive force in the thickness direction using a heating and pressurizing device F configured to be capable of heating. For example, the heating and pressing device is composed of two flat plates Z, Z. The two flat plates Z, Z are respectively arranged to sandwich the second stage H, the substrate (ceramic insulating layer D, copper die pad E, and copper thin layer F), and the multiple semiconductor chips B temporarily fixed to the copper die pad E via the pieces 2' of the sintered bonding layer. Then, the separation distance between the two heated flat plates is reduced to apply pressure (press) to the multiple members, thereby heating the pieces 2' of the sintered bonding layer while pressing them. By carrying out the heating step in this manner, the pieces 2' of the sintered bonding layer can be heated while being pressed, so that the semiconductor chip B can be firmly bonded to the substrate (copper die pad E) via the pieces 2' of the sintered bonding layer. This improves the bonding reliability of the semiconductor chip B to the substrate. After carrying out the heating step in this manner, bonding wires may be bonded to required locations. A jig for arranging a plurality of substrates may be disposed between the lower flat plate Z and the copper die pad E shown in FIG. 4A.

[0099] On the other hand, in the heating step, after all the semiconductor chips B to be bonded are temporarily fixed, the second stage H may be heated without applying a compressive force in the thickness direction to the pieces 2' of the sintered bonding layer, as shown in Fig. 4B. At this time, the second stage H is heated at a temperature at which the sinterable particles contained in the pieces 2' of the sintered bonding layer can be sintered (for example, any temperature in the range of 200°C to 400°C). Even when such a heating step is performed, the semiconductor chip B can be firmly bonded to the substrate (copper die pad E) via the piece 2' of the sintered bonding layer. Therefore, the bonding reliability of the semiconductor chip B to the substrate can be improved. By carrying out the heating step as described above, the heating and pressurizing device F for applying a compressive force to the individual pieces 2' of the sintered bonding layer is not required, so that the manufacturing equipment can be made simpler.

[0100] In the method for manufacturing a semiconductor device according to this embodiment, further steps may be carried out. For example, a wire bonding step may be performed to electrically connect a part of the semiconductor chip B to a part of the substrate. In addition, a sealing process may be performed in which the semiconductor chip B and the individual pieces 2' of the sintered bonding layer are sealed with a thermosetting resin such as an epoxy resin. In the sealing process, a heat treatment is performed at a temperature of, for example, 150° C. or higher and 200° C. or lower to promote a curing reaction of the thermosetting resin.

[0101] In the manufacturing method of the semiconductor device according to this embodiment, as described above, a sintering process is performed in which a compressive force is applied in the thickness direction to the individual piece 2' of the sintered bonding layer while heating it, thereby bonding the individual piece 2' of the sintered bonding layer to the substrate. As described above, in the observation image of the surface of the sintered bonding layer 2, the maximum size of the voids observed is 100 μm or less in the observation image at 100 times magnification. 2 In this range, the area ratio of the voids is 5.0% or less. Since the sintered bonding layer 2 has such a configuration, the maximum size of the voids is small, and in some cases, the voids are almost absent. Therefore, the maximum size of the voids in the sintered bonding layer 2 after the sintering process is also small, and in some cases, the voids may disappear. Therefore, even if the sintered bonding layer 2 is subjected to repeated increases and decreases in temperature during use, peeling due to the voids can be suppressed at least in a part of the interface between the sintered bonding layer 2 and the adherend. In addition, the occurrence of cracks due to the voids can be suppressed at least inside the sintered bonding layer 2. Therefore, even if the sintered bonding layer 2 is subjected to repeated increases and decreases in temperature during use, the bond between the sintered bonding layer 2 and the adherend can be sufficiently maintained.

[0102] The sheet for sinter bonding of this embodiment is as exemplified above, but the present invention is not limited to the sheet for sinter bonding exemplified above. That is, various forms used in general sheets for sinter bonding and the like can be adopted as long as they do not impair the effects of the present invention.

[0103] The matters disclosed in this specification include the following. (1) A sheet for sintering comprising a sintering bonding layer including sinterable particles containing a conductive metal and an organic binder, A sheet for sinter bonding, in which in an image of the surface of the sinter bonding layer observed at 100x magnification, the maximum size of the voids observed is 100 µm or less. (2) At least 9 mm 2 The sheet for sinter bonding according to (1) above, wherein the area ratio of the voids is 5.0% or less within the range. (3) The complex viscosity of the sintered bonding layer is 3×10 at 25° C. 5 [Pa·s] or more 3×10 11 The sheet for sintering according to (1) or (2) above, having a viscosity of 100 Pa·s or less. (4) The complex viscosity of the sintered bonding layer is 3×10 at 93° C. 4 [Pa·s] or more 3×10 10 The sheet for sintering bonding according to any one of (1) to (3) above, having a viscosity of 100 [Pa·s or less]. (5) The sheet for sintering bonding according to any one of (1) to (4) above, wherein the average particle size of the sinterable particles is 1 nm or more and 10,000 nm or less, preferably 50 nm or more and 500 nm or less. (6) The sintering bonding sheet according to any one of (1) to (5) above, wherein the sintering bonding layer contains, as the organic binder, a first organic binder and a second organic binder having a smaller molecular weight than the first organic binder. (7) The sintering bonding sheet according to (6) above, wherein the first organic binder is a thermally decomposable polymer binder. (8) The sintering bonding sheet according to any one of (1) to (7) above, wherein the sintering bonding layer contains the sinterable particles in an amount of 60% by mass or more and 99% by mass or less. (9) The sintering bonding sheet according to any one of (1) to (8) above, wherein the sintering bonding layer contains the organic binder in an amount of 1 mass % to 40 mass %. (10) A method for producing a sheet for sintering according to any one of (1) to (9) above, preparing a varnish containing the sinterable particles, the organic binder, and an organic solvent; and producing the sinter-bonding layer by volatilizing the organic solvent from the varnish. EXAMPLES

[0104] The present invention will now be described in more detail with reference to experimental examples. However, the following examples are intended to explain the present invention in more detail and are not intended to limit the scope of the present invention.

[0105] (raw material for sintered bonding layer) [Sinterable particles] ·First silver particles: Average particle size: 60 nm, manufactured by DOWA Electronics ·Second silver particles: Average particle size: 1100 nm, manufactured by Mitsui Mining & Smelting Co., Ltd. [Organic binder] First organic binder (thermolybdic polymer binder): Polycarbonate resin: (Biphenyl type phenolic resin, phenol equivalent: 209g / eq) Product name: "QPAC40" manufactured by Empower Materials · Second organic binder (easily volatile binder): Isobornylcyclohexanol Product name: Tersolv MTPH, manufactured by Nippon Terpene Chemical Co., Ltd. · Organic solvent: Methyl ethyl ketone (MEK) (Support layer) Release film (product name "MRA38", manufactured by Mitsui Plastics Co., Ltd.)

[0106] Example 1 A varnish was prepared by dissolving or suspending the first silver particles, the second silver particles, the first organic binder (polycarbonate resin), and the second organic binder (isobornylcyclohexanol) in methyl ethyl ketone (MEK) in the composition shown in Table 1. More specifically, a hybrid mixer (model "HM-500", manufactured by Keyence Corporation) was used to stir the mixture for 3 minutes in stirring mode. Next, a varnish was applied to the release-treated surface of the support layer, and then the support layer was heated at 110° C. for 3 minutes to form a sinter-bonding layer on the support layer. In this way, an intermediate sheet for sinter-bonding was produced. Next, the two intermediate sheets for sinter bonding were bonded together so that the sinter bonding layers overlapped each other, to produce a sheet for sinter bonding having a sinter bonding layer with a thickness of 50 μm. In Table 1, the blending amounts of the first silver particles and the second silver particles are shown as amounts at the time of charging, and in Table 2, the blending amount of the sinterable particles is shown as ash content value.

[0107] [Table 1] [Table 2]

[0108] The viscosity of each of the varnishes of Composition A, Composition B, and Composition C was measured according to the measurement conditions described above.

[0109] (Examples 2 to 7) Except for changing the blending composition to that shown in Table 3, the same procedure as above was followed to produce each of the sinter-bonding sheets.

[0110] (Comparative Examples 1 and 2) Except for changing the blending composition to that shown in Table 3, the same procedure as above was followed to produce each of the sinter-bonding sheets.

[0111] Table 3 shows the composition and physical properties of the sinter-bonding sheets in each of the examples and comparative examples.

[0112] [Table 3]

[0113] <Physical properties of sinter bonding sheet (sinter bonding layer)> The surfaces of the sinter bonding layers of the sinter bonding sheets produced as described above were observed and their physical properties were measured as described below.

[0114] [Complex viscosity of sintered bonding layer] The complex viscosity of the sintered bonding layer was measured under the following measurement conditions. Test piece cut from sintered bonded layer: Length 30mm, width 5mm Measurement equipment: Dynamic viscoelasticity measuring equipment (Product name: "RSA-G2" (manufactured by TA Instruments, etc.) Measurement mode: Tensile mode Initial chuck distance: 20mm Pulling speed: 1mm / sec Measurement temperature: 10℃ to 100℃ (heating rate: 5℃ / min) Read the complex viscosity (complex viscosity coefficient η*) value [Pa s] at least at 25℃

[0115] [Surface observation and image analysis of sintered bonded layer] Equipment used: Digital microscope, device name "VHX-2000" manufactured by Keyence Corporation Lens: Z20 set to 100x Shutter speed: 1 / 60 [sec] Gain: 0 [dB] Lighting: Lamp ON (about 90%), Stage transmitted light ON (about 20%) Frame rate: 15 "F / s" The images were taken under the above conditions. In addition, a histogram of saturation was extracted from the images taken (extraction range: saturation 0-50) to obtain an observation image. Image analysis was performed using the automatic area measurement function of the device used. The area of ​​the image subjected to image analysis was approximately 9.7 mm 2 From the analysis results, the maximum size of the multiple voids and the total area ratio of the voids were calculated. As mentioned above, the size of each void is the distance when a straight line is drawn between the two points that are the furthest from each other. FIG. 5 shows examples of images (Examples 1 to 4 and Comparative Examples 1 and 2) after the observed images were binarized for image analysis.

[0116] <Reliability evaluation of sinter bonding sheets (sinter bonding layers)> In order to confirm the likelihood of peeling occurring at a portion of the interface between the sintered bonding layer and the adherend after repeated temperature increases and decreases, the sintered bonding layer of each sintered bonding sheet manufactured as described above was evaluated as follows. In summary, a laminate (package) having a sintered bonding layer was assembled, and then a temperature cycle test was performed on the laminate, and the bonding state of the sintered bonding layer was evaluated by ultrasonic inspection images. The details are as follows. A Cu substrate (20 mm x 20 mm x 3 mm) plated with Ag at a thickness of 5 μm and a Si chip (5 mm x 5 mm x 0.2 mm) plated with Ti (0.1 μm) / Ag (0.75 μm) were prepared. Each sintered bonding layer was sandwiched between the Cu substrate and the Si chip to produce a laminate, which was then subjected to a sintered bonding process under the conditions of 300°C / 10 MPa / 2.5 minutes. For the laminate after the sintering process, the bonding condition (area of ​​the region where the sintered bonding layer is bonded) at the interface between the Cu substrate and the sintered bonding layer, and at the interface between the Si chip and the sintered bonding layer was evaluated using ultrasonic inspection images (initial evaluation). Equipment: "FineSAT200" manufactured by Hitachi Power Solutions Probe: PQ2-50-13 (reflection mode) Number of measurement points: 600 x 600 (within a square area of ​​21 mm on each side) After the above initial evaluation, the laminate was placed in a temperature cycle tester, and an accelerated deterioration test was carried out by repeatedly increasing and decreasing the temperature under the following conditions. Temperature conditions: -40℃ / 200℃ (repeated every 15 minutes without leaving it at room temperature) Number of cycles: 1000 cycles The laminate after the accelerated degradation test was evaluated using ultrasonic flaw detection images in the same manner as above. Specifically, the evaluation was performed using image analysis software ("Image J"), and the bonded area obtained by the initial evaluation was compared with the bonded area obtained by the evaluation after the accelerated degradation test. If the bonded area in the initial evaluation was taken as 100%, when the bonded area after the accelerated degradation test was less than 50% (when peeling of the sintered bonding layer progressed to more than half of the bonded area), the reliability evaluation was judged to be "poor". Otherwise, it was judged to be "good".

[0117] As can be seen from the above evaluation results, the sintered bonding layer of the sintered bonding sheet of the embodiment was able to suppress peeling at a part of the interface between the sintered bonding layer and the adherend even when used in an environment where the temperature repeatedly rises and falls. That is, it had good bonding reliability. In addition, the sintered bonding layer of the sintered bonding sheet of the embodiment also had good thermal conductivity and electrical conductivity. On the other hand, the sintered bonding layer of the sintered bonding sheet of the comparative example did not have good bonding reliability. [Industrial Applicability]

[0118] The sheet for sintering bonding of the present invention is suitably used, for example, as an auxiliary tool for manufacturing semiconductor devices. [Explanation of symbols]

[0119] 10: Sintering bonding sheet, 1: supporting layer; 2: sintered bonding layer; A: Collet, B: Semiconductor chip, C: Dicing tape, D: ceramic insulating layer, E: copper die pad, F: copper thin layer, G: first stage, H: second stage.

Claims

1. A sheet for sintering comprising a sintering bonding layer including sinterable particles containing a conductive metal and an organic binder, A sheet for sinter bonding, in which in an image of the surface of the sinter bonding layer observed at 100x magnification, the maximum size of the voids observed is 100 μm or less.

2. At least 9 mm 2 The sheet for sinter bonding according to claim 1 , wherein the area ratio of the voids is 5.0% or less in the range of 1.

3. The complex viscosity of the sintered bonding layer is 3.0×10 at 25° C. 6 [Pa・s] or more 3.0×10 10 The sinter-bonding sheet according to claim 1 or 2, wherein the viscosity is [Pa·s] or less.

4. The sinter bonding sheet according to claim 1 or 2, wherein the sinter bonding layer contains the sinterable particles in an amount of 60% by mass or more and 99% by mass or less.

5. The sintering bonding sheet according to claim 1 or 2, wherein the average particle size of the sinterable particles is 50 nm or more and 500 nm or less.

Citation Information

Patent Citations

  • Sheet for heat joining and sheet for heat joining with dicing tape

    JP2017066384A